Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.4 - Multiplying Polynomials - 4.4 Exercises: 112

Answer

$x^{3}-3x^{2}-9x+27$

Work Step by Step

We are given that $f(x)=x^{2}-9$, $g(x)=2x$, and $h(x)=x-3$. We know that $(fh)(x)=f(x)\times h(x)$. Therefore, $(fg)(x)=(x^{2}-9)\times(x-3)$. We can use the FOIL method to further simplify this function. First terms: $x^{2}\times x=x^{2+1}=x^{3}$ Outer terms: $x^{2}\times-3=-3x^{2}$ Inner terms: $-9\times x=-9x$ Last terms: $-9\times-3$ Add together: $x^{3}+(-3x^{2})+(-9x)+27=x^{3}-3x^{2}-9x+27$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.